Al-Co-Ce glass forming alloys and their corrosion behaviour - Li, Chunling (2014)
There is growing interest in Al-TM (transition metal)-RE (rare earth) amorphous alloys because of the combination of their good mechanical properties and corrosion resistance. However, the high critical cooling rate required to form the amorphous structure leads to difficulties in generating bulk amorphous material. Therefore, there has been greater interest in producing amorphous Al-TM-RE alloys as surface layers. In this study, wedge mould casting, laser surface melting (LSM) and large area electron beam (LAEB) surface melting were used to fabricate Al Co-Ce alloys in both crystalline and amorphous form. An eutectic Al 33Cu (wt.%) alloy was also used to quantify the solidification conditions based on the well-known relationship.